If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 2(b + -3) = -9 Reorder the terms: 7 + 2(-3 + b) = -9 7 + (-3 * 2 + b * 2) = -9 7 + (-6 + 2b) = -9 Combine like terms: 7 + -6 = 1 1 + 2b = -9 Solving 1 + 2b = -9 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2b = -9 + -1 Combine like terms: 1 + -1 = 0 0 + 2b = -9 + -1 2b = -9 + -1 Combine like terms: -9 + -1 = -10 2b = -10 Divide each side by '2'. b = -5 Simplifying b = -5
| 2x^2-6x-8=8 | | x(5x+3)=2x^2-5x+3 | | 62-x=281 | | -7-9x=-61g | | x=13/8 | | 0.2(4x+32)=0.8(x+8) | | 2-x+9=8 | | 151-y=260 | | 13/8= | | -4+y=-0.5x | | 3=7(y-7) | | 6c+24=4c-1 | | 200W^2+W-20=0 | | 256=18-x | | 15a+16a+7a= | | 7x-27=-22 | | 7x+2y=190 | | 2z-8=7z+9 | | 18=.32w | | (s-8)+5=10 | | 5-x-2=5 | | 9x+8=9(x+1) | | 8-2x=7+3x | | 3x+6y=304 | | y=-9x+15 | | 8/8=13/8 | | 7x+1=3x-35 | | 5=.05w | | 16+8b=4(5b-5) | | (x(-7+i))(x(-7-i))(x+2)=y | | n/9-4=4 | | 6xy+8xy= |